2023
DOI: 10.48084/etasr.5483
|View full text |Cite
|
Sign up to set email alerts
|

ANN and GRNN-Based Coupled Model for Flood Inundation Mapping of the Punpun River Basin

Abstract: The Punpun River is primarily a rain-fed river. Forecasting rainfall accurately would enable an early evaluation of drought and flooding conditions. Therefore, having a flawless model for predicting rainfall is important for the hydrological analysis of any river basin. In this study, Artificial Neural Network (ANN)-based models were developed to predict rainfall and discharge in the basin. During the rainy season, water is spread in and around the area of the watershed, thus a General Regression Neural Networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In conclusion, the ANN model presented in this study demonstrated its effectiveness in predicting the mechanical properties of 3D-printed parts. By leveraging the capabilities of ANNs, significant advancements can be made in many fields [22][23][24], and in this case, the field of additive manufacturing, leading to enhanced product performance and increased efficiency. Future research can explore further applications of ANNs in optimizing other aspects of the 3D printing process, such as material selection, geometry optimization, and process parameter tuning, to unlock the full potential of this innovative technology.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the ANN model presented in this study demonstrated its effectiveness in predicting the mechanical properties of 3D-printed parts. By leveraging the capabilities of ANNs, significant advancements can be made in many fields [22][23][24], and in this case, the field of additive manufacturing, leading to enhanced product performance and increased efficiency. Future research can explore further applications of ANNs in optimizing other aspects of the 3D printing process, such as material selection, geometry optimization, and process parameter tuning, to unlock the full potential of this innovative technology.…”
Section: Discussionmentioning
confidence: 99%